2010
DOI: 10.2353/ajpath.2010.090564
|View full text |Cite
|
Sign up to set email alerts
|

Lack of CXC Chemokine Receptor 3 Signaling Leads to Hypertrophic and Hypercellular Scarring

Abstract: CXC chemokine receptor 3 (CXCR3) signaling promotes keratinocyte migration while terminating fibroblast and endothelial cell immigration into wounds; this signaling also directs epidermal and matrix maturation. Herein, we investigated the long-term effects of failure to activate the "stop-healing" CXCR3 axis. Full-thickness excisional wounds were created on CXCR3 knockout((-/-)) or wild-type mice and examined at up to 180 days after wounding. Grossly, the CXCR3(-/-) mice presented a thick keratinized scar comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
88
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(90 citation statements)
references
References 40 publications
(79 reference statements)
2
88
0
Order By: Relevance
“…95 In the absence of CXCR3, wounds remained immature with an inflammatory milieu and went on to develop a hypertrophic scar phenotype, similar to those observed in humans. 95 Taking this idea to its logical conclusion, the authors postulated that transplantation of normal fibroblasts to a CXCR3 -/-wound may lead to the correction of fibroblast-generated matrix dysfunction, resulting in improved healing. Not only did these normal fibroblasts survive within the wound milieu, they had a positive effect on healing, including matrix remodeling, improved collagen alignment, and increased tensile strength.…”
Section: 117mentioning
confidence: 81%
See 3 more Smart Citations
“…95 In the absence of CXCR3, wounds remained immature with an inflammatory milieu and went on to develop a hypertrophic scar phenotype, similar to those observed in humans. 95 Taking this idea to its logical conclusion, the authors postulated that transplantation of normal fibroblasts to a CXCR3 -/-wound may lead to the correction of fibroblast-generated matrix dysfunction, resulting in improved healing. Not only did these normal fibroblasts survive within the wound milieu, they had a positive effect on healing, including matrix remodeling, improved collagen alignment, and increased tensile strength.…”
Section: 117mentioning
confidence: 81%
“…67,92,93 It is proposed that this signaling axis allows wounds to transition through remodeling resulting in the characteristic appearance of scar tissue with densely packed collagen bundles and reduced elastin. 94,95 Wound contraction secondary to myofibroblast action begins in the proliferative phase, but continues during remodeling.…”
Section: Remodeling Phasementioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, delays in wound re-epithelialization were associated with enhanced wound fibrosis, possibly due to a lack of signaling from epidermis, which may play a role in hypertrophic scar development. 135,149 Studies in co-culture models have demonstrated that many fibroblast genes are regulated by keratinocytederived factors, including genes coding for growth factors, ECM components, and MMPs, 136 all vital constituents for successful wound healing. Integrin a 3 b 1 is an intriguing candidate for influencing keratinocyte-to-fibroblast crosstalk in cutaneous wounds, given its above described role in promoting keratinocyte-to-endothelial cell crosstalk.…”
Section: Epidermis-mediated Modulation Of the Wound Microenvironmentmentioning
confidence: 99%